Employing artistic embodiment in the supplications of Imam Al-Sajjad  - موسی عربي; حسین مهتدي; مهدي تركشوند (آداب الكوفة, 2017)
The supplications of Imam Al-Sajjad B constitute an important part of our religious literature, and it is a means of communicating with the idol and expressing the feelings and feelings that stir in the heart. The existence of deep abstract and spiritual concepts, as well as the sentimental and emotional nature of these supplications, led Imam Al-Sajjad B to convey the message of supplication to the addressee in the best way, with a prominent and artistic expression. One of the expressive and artistic methods that would have achieved this important matter